Valerianella turcica (Caprifoliaceae), a new species from Turkey - Doǧru-Koca, Asli; Zare, Golshan; Çeçen, Ömer (Phytotaxa, 2016)
Valerianella turcica, a new species from central Anatolia, Turkey, is described and illustrated. Morphologically, this new species is characterized by the combination of an inflated and regularly 6-lobed fruiting calyx with erect, triangular, aristate, and hooked lobes. Additional details on its geographical distribution, conservation status, and comparisons to related species are also provided.